Sustainability Reporting from the Perspective of IFRS S1 and IFRS S2: A Bibliometric Study - Loso Judijanto; Bintang Cahya; Rully Fildansyah (Westscience Press, 2026)
Since the International Sustainability Standards Board (ISSB) issued IFRS S1 and IFRS S2 in June 2023, sustainability reporting has entered a phase of accelerated standardization. This study conducts a bibliometric analysis to investigate the intellectual structure, publication trends, influential authors, and collaboration patterns of research examining sustainability reporting from the perspective of IFRS S1 and IFRS S2. Data were retrieved from Scopus using keyword combinations built around